2015
DOI: 10.5750/ijpcm.v5i3.517
|View full text |Cite
|
Sign up to set email alerts
|

Decision Aids in the United States: the Patient Response

Abstract: Background:  In the United States and elsewhere, a growing chorus of voices is calling for the routine use of patient decision aids (DAs) and shared decision making (SDM) in day-to-day care.  A frequently cited barrier to this approach is the belief that many patients will not be able to understand key clinical information and/or prefer to delegate decision making to providers.  These beliefs, often held by providers, are thought to be particularly applicable to elderly and less educated patients.Objectives: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The reporting was not sufficiently detailed to permit a pooled analysis . A cohort study of 3001 patients participating in SDM with pDAs in 6 US primary care practices found similar positive reactions and improvements in knowledge across the spectrum of age, sex, and educational level, but the study included too few Black, Indigenous, and Latinx individuals to enable making separate conclusions for these populations …”
Section: Generalizability Of Sdmmentioning
confidence: 99%
“…The reporting was not sufficiently detailed to permit a pooled analysis . A cohort study of 3001 patients participating in SDM with pDAs in 6 US primary care practices found similar positive reactions and improvements in knowledge across the spectrum of age, sex, and educational level, but the study included too few Black, Indigenous, and Latinx individuals to enable making separate conclusions for these populations …”
Section: Generalizability Of Sdmmentioning
confidence: 99%